2014
DOI: 10.1016/j.jtcvs.2013.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Surgical risk algorithm as a measure of successful adoption of transapical transcatheter aortic valve implantation

Abstract: Only after a protracted learning curve did the anticipated benefits of transapical TAVI materialize for patients at high risk for surgery as predicted by the STS risk algorithms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…As such, the risk of both false positive and false negative results must be considered. Furthermore, it represents our initial learning experience with the transapical technique; however, we feel that our learning experience is consistent with other reports . As it relates to this study, the learning process is most evident in the significant decrease in the prevalence of conduit use during the second half of the study.…”
Section: Discussionsupporting
confidence: 89%
“…As such, the risk of both false positive and false negative results must be considered. Furthermore, it represents our initial learning experience with the transapical technique; however, we feel that our learning experience is consistent with other reports . As it relates to this study, the learning process is most evident in the significant decrease in the prevalence of conduit use during the second half of the study.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed in the PARTNER RCT, the median number of TA-TAVR procedures was 4 (range, 1–20; Supplementary Appendix Figure 1). Recent studies have reported that the number of cases required to overcome the learning curve ranges from 18–100, 1517 a level that far exceeded the experience of virtually all of the PARTNER centers at the time of the RCT. The current analysis was therefore performed to determine whether the HRQoL outcomes of TA-TAVR have improved with increasing operator and center experience.…”
Section: Discussionmentioning
confidence: 99%
“…The reported number of cases required to overcome the learning curve varies from 18 to 100 . Alli et al reported a shorter learning curve associated with the transapical procedure (18 cases) in comparison to the transfemoral procedure (36 cases); while Lichtenstein, D'Ancona, and colleagues reported much greater cases numbers (70 and 100, respectively) required to overcome the learning curve associated with the transapical procedure . The numbers needed to obtain proficiency are unfortunately not known and not universally accepted.…”
Section: Discussionmentioning
confidence: 99%
“…A learning curve has been reported for transcatheter aortic valve replacement. [7][8][9][10] To compensate for the learning curve associated with transcatheter valve replacement, the last 200 cases were selected for study and included 100 patients each in the transfemoral and transapical access groups. Patients underwent surgery from May 2011 through August 2013.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation